TRANSPARANSI DAN AKUNTABILITAS PELAYANAN PUBLIK KASUS TEKNOLOGI PENGELOLAAN AIR BERSIH DAN AIR LIMBAH DOMESTIK - Komarudin, Komarudin; Yudo, Satmoko (Jurnal Air Indonesia, 2009)
Bureaucracy reform of public service delivery requires a fast prime, precisely, accurate, and affordable. Some of the important elements of public service delivery, among others, providing guidance services, service standards, service standards at least, one of the doors and a roof, transparency, and accountability. Information on water technology and water management, and need to be provided through public services and the prime quality, transparent and accountable, in order to support efforts to reform the bureaucracy to uphold the principles of good governance. Key words: Transparency and accountability, public services, water and waste water technolgy management.